2020
DOI: 10.3390/jcm9092974
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Impact of Sarcopenic Obesity after Neoadjuvant Chemotherapy Followed by Surgery in Elderly Patients with Esophageal Squamous Cell Carcinoma

Abstract: We evaluated the impact of body composition on clinical outcomes after neoadjuvant chemotherapy (NAC) followed by surgery for elderly cStage II/III esophageal squamous cell carcinoma (ESCC). Ninety-one patients ≥70 years old and 116 patients <70 years old with ECSS who underwent NAC between January 2013 and June 2018 at the Aichi Cancer Center were included. Body composition as assessed from computed tomography (CT), American Society of Anesthesiologists physical status (ASA-PS), and subjective global asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 34 publications
(45 reference statements)
2
15
0
Order By: Relevance
“…This study showed that patients older than 65 years with sarcopenia were associated with worse OS, which was meaningful and different from other similar reports. Some study showed sarcopenic obesity was an independent predictor of prognosis in elderly patients (>70 years) received NAT followed by surgery for elderly cStage II/III esophageal squamous cell carcinoma (ESCC) ( 37 ). But these patients often had little change in weight and were not easy to be diagnosed with sarcopenic obese.…”
Section: Discussionmentioning
confidence: 99%
“…This study showed that patients older than 65 years with sarcopenia were associated with worse OS, which was meaningful and different from other similar reports. Some study showed sarcopenic obesity was an independent predictor of prognosis in elderly patients (>70 years) received NAT followed by surgery for elderly cStage II/III esophageal squamous cell carcinoma (ESCC) ( 37 ). But these patients often had little change in weight and were not easy to be diagnosed with sarcopenic obese.…”
Section: Discussionmentioning
confidence: 99%
“…30 Because sarcopenia-associated obesity represents a well-established risk factor for a worse postoperative course, this could explain our results. 31 The first reported procedure of MIE in the prone position without OLV was by Bonavina et al 32 In their study, the authors found improved oxygenation and reduced shunt fraction in the prone position. These results were confirmed by Saikawa et al 33 Although ventilation strategies in MIE in the prone position without OLV are of limited use in the operating theatre, we found that protective ventilation was safe and feasible, with no major complications such as severe hypoxemia or hypercapnia.…”
Section: Discussionmentioning
confidence: 99%
“…found contradictory results showing that only sarcopenia (cut-offs for total muscle mass at L3 level: 42.2 cm 2 /m 2 for men and 33.9 cm 2 /m 2 for women) was a marker of impaired survival in patients with pancreatic adenocarcinoma, not sarcopenic obesity (obesity defined as VAT / total adiposity ratio > 2 at the L3 level). Elderly patients with esophageal squamous cell carcinoma (ESCC) treated with neoadjuvant chemotherapy (NAC) who were affected by SOB (sarcopenia: skeletal muscle index < 42.0 cm 2 / m 2 in men and < 38.0 cm 2 / m 2 in women, obesity: VAT > 100 cm 2 ), not sarcopenia, had a worse survival in comparison to patients without SOB [153]. Another study with patients with ESCC and esophageal adenocarcinoma indicated that the presence of sarcopenia or sarcopenic obesity was not associated with impaired short-or long-term survival [154].…”
Section: Sarcopenic Obesitymentioning
confidence: 99%